A small scale wind power generation - Richard Wong Chung Hie (School of Electrical System Engineering, University Malaysia Perlis, 2011)
A small scale wind power generation has been designed and developed in this final year project. The small scale wind power generation been developed which almost of 100:1 ratio than wind turbine by using the same concept of wind energy convert to the electrical power. This small scale wind power generation has been developed in vertical axis type; it generates electricity when the wind blowing to the blades and the blades will rotate the rotor and generator which are link together. The generator will generate the amount of electric by consideration the speed of rotor rotate when the wind blowing. This project will include the calculation formula such as Betzs Elementary Momentum theory, tip speed ratio and power coefficient which effect by the rotor diameter, number of blades, and width of blade. This calculation will compare with the result from the developed hardware. Matlab software will use in this project. The software will simulate the wind power generation system and the graph of the relationship between wind speed and power.